The artist - Vere, Ed 1973- (Doubleday Books for Young Readers, 2023)
A brave little artist goes on an epic adventure to share her creativity with the world, adding color and life to a drab, gray city
Simultaneously published in the United Kingdom by Puffin Books, London, 2023
Keywords: Kreativität; Dinosaurier; Malerei; Painting / Juvenile fiction; Creative ability / Fiction; Peinture / Romans, nouvelles, etc. pour la jeunesse; Créativité / Romans, nouvelles, etc; Dinosaurs / Juvenile fiction; Bilderbuch